Fault Characteristics and Control Strategies of Multiterminal High Voltage Direct Current Transmission Based on Modular Multilevel Converter. (18th October 2015) - Chang, Fei; Yang, Zhongping; Wang, Yi; Lin, Fei; Liu, Shihui
Abstract : The modular multilevel converter (MMC) is an emerging voltage source converter topology suitable for multiterminal high voltage direct current transmission based on modular multilevel converter (MMC-MTDC). This paper presents fault characteristics of MMC-MTDC including submodule fault, DC line fault, and fault ride-through of wind farm integration. Meanwhile, the corresponding protection strategies are proposed. The correctness and effectiveness of the control strategies are verified by establishing a three-terminal MMC-MTDC system under the PSCAD/EMTDC electromagnetic transient simulation environment.